COMPARED LAW ISSUES REGARDING THE JUDGE SUPERVISING THE LIMITATION OF FREEDOM - Gabriela-Nicoleta CHIHAIA (Challenges of the Knowledge Society)
According to Law no. 254/2013 regarding the execution of sentences and custodial measures ordered by the court during the criminal trial, the judge that oversees the limitation of freedom process to monitor and control the execution of sentences and ensures the legality of custodial measures. Although Spanish and Italian law systems influenced the institution of this judge it did not copy the regulation from this countries, but continues the line started in our country by Law no. 275/2006, which regulated the judge delegated for the execution of custodial sentences. This study aims without trying to be exhaustive, to present different models adopted by European countries in the matter of justices that control the activity during the execution of custodial sentences. Thus we analyzed the laws of Italy, Spain and Germany. Without trying to prioritize these European regulations, the paper aims to present the legal nature of the activity of this type of justice in relation to the regulated activity of the Romanian legislation, which mentions that his or hers responsibilities are administrative and also administrative jurisdictional. We also note the similarities between the powers of this type of judge in the European countries presented, regarding, for example, the complaints of inmates against prison conditions or infringements of their rights, but at the same time the difference which will be highlighted in particular in relation to the status of these judges. In the last part of the paper we present a number of problems and we propose possible solutions to their law by adopting new legal provisions taken from the laws of the European countries analyzed in this study.